2012
DOI: 10.1210/jc.2011-3425
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Body Mass Index Is a Predictor of Neonatal Hypoglycemia in Gestational Diabetes Mellitus

Abstract: Pregestational BMI should be considered among the predictors of NH in offspring of women with GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 22 publications
3
24
2
3
Order By: Relevance
“…This could have contributed to the heterogeneity of study conclusions. There are many other risk factors for neonatal hypoglycaemia, such as small‐for‐gestational‐age or large‐for‐gestational‐age neonates, preterm delivery, maternal BMI and third trimester glycaemic control that have confounded the relationship between maternal and neonatal glucose . None of the six studies that consistently found a relationship between neonatal hypoglycaemia and intrapartum glucose included an analysis that adjusted for potential confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…This could have contributed to the heterogeneity of study conclusions. There are many other risk factors for neonatal hypoglycaemia, such as small‐for‐gestational‐age or large‐for‐gestational‐age neonates, preterm delivery, maternal BMI and third trimester glycaemic control that have confounded the relationship between maternal and neonatal glucose . None of the six studies that consistently found a relationship between neonatal hypoglycaemia and intrapartum glucose included an analysis that adjusted for potential confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Im Gegensatz zu anderen Komplikationen einer diabetischen Fetopathie [22] korreliert das Risiko für postnatale Hypoglykämien nicht ohne weiteres mit der mütterlichen Stoffwechsellage gegen Ende der Schwangerschaft. Ein im letzten Trimenon wieder abfallender HbA1c-Wert kann sogar mit einem erhöhten Risiko für eine postnatale Hypoglykämie einhergehen [23]. Dies ist als Folge der wachsenden Insulinsekretionsleistung der fetalen β-Zellen und einer höheren Gesamtmasse insulinsensitiven Gewebes im Feten mit entsprechend höherem materno-fetalen Glukosetransfer zu werten.…”
Section: Diabetische Fetopathieunclassified
“…6,7 A secondary analysis of the HAPO study as well as other studies have found that neonatal fat mass, fetal hyperinsulinemia, and neonatal hypoglycemia are positively related to maternal size after adjustment for maternal glycemia. 5,[8][9][10] In the original HAPO observational study, LGA birth weight, umbilical cord serum c-peptide, and neonatal fat mass were all increased in a continuous fashion with maternal glucose values. This was true even at maternal glucose levels below thresholds typically used for diagnosis of diabetes during pregnancy.…”
mentioning
confidence: 99%